Data and device protection: A ToF‐SIMS, wetting, and XPS study of an Apple iPod nano. (6th December 2013) - Gupta, Vipul; Tuscano, Joshua A.; Romriell, Naomi R.; Davis, Robert C.; Linford, Matthew R.
<x xml:space="preserve">Abstract</x> An important aspect of the robustness of an electronic device is its ability to resist water, fingerprints, dirt, and smudges that may compromise its ability to function and/or the information within it. Here, we report a chemical analysis by ToF‐SIMS, wetting, and XPS of the surfaces in a commercially available Apple iPod nano (8GB, MC525LL/A), which showed good resistance to its environment. This analysis reveals that the front panel (touchscreen) of the device is coated with a low free energy fluorinated polymer that may consist of short segments of a fluorinated hydrocarbon connected through ether linkages. No other part of the device appears to have this hydrophobic coating. A plasma treatment of the device leads to a deterioration of its performance. This work demonstrates how different analytical techniques can complement each other and contribute to a better understanding of a surface or a material. Copyright © 2013 John Wiley & Sons, Ltd.